Antisemitism in American Healthcare: The Role of Workplace Environment - Fishman, Alexandra Chana (Journal of religion and health, 2026)
A rise in antisemitism has been well documented since the Hamas war on Israel on October 7th, 2023. However, there has been a dearth of literature on antisemitism in healthcare. This pilot study asked Jewish healthcare professionals (N = 645) to self-report their experiences with antisemitism in their work environments. The article explores the degree to which the odds that a respondent reports experiencing antisemitism increase or decrease is influenced by their colleagues' and administrators' ability to identify antisemitism, the type of workplace, and age. The results of a binary logistic regression show that the odds of a Jewish healthcare professional experiencing antisemitism decreases when they state that their colleagues and administration can identify antisemitism (OR = .56 95%CI 0.41-0.76 p < .01). Additionally, there is a significant increase in the odds of experiencing antisemitism for Jewish healthcare professionals employed in academic medical centers compared to those employed in community hospitals (OR = 4.81 95% CI 2.42-9.54 p < .01). Antisemitism is rampant in healthcare. The workplace environment, along with colleagues’ and administrators’ ability to recognize and address antisemitism, significantly impacts Jewish professionals' experiences in healthcare.